Comparison of transection techniques in pediatric major hepatectomy: a matched pair analysis - Fuchs, Juri; Ruping, Fabian; Murtha-Lemekhova, Anastasia; Kessler, Markus; Günther, Patrick; Mehrabi, Arianeb; Hoffmann, Katrin (HPB, 2023)
Background - Evidence on safety and efficacy of different liver transection techniques in pediatric major hepatectomy is completely lacking, as no study has been conducted so far. The use of stapler hepatectomy has never before been reported in children. - Methods - Three liver transection techniques were compared: (1) ultrasonic dissector (CUSA), (2) tissue sealing device (LigaSure™), and (3) stapler hepatectomy. All pediatric hepatectomies performed at a referral center in a 12-year study period were analyzed, patients were pair-matched in a 1:1:1-fashion. Intraoperative weight-adjusted blood loss, operation time, use of inflow occlusion, liver injury (peak-transaminase levels), postoperative complications (CCI), and long-term outcome were compared. - Results - Of 57 pediatric liver resections, 15 patients were matched as triples based on age, weight, tumor stage, and extent of resection. Intraoperative blood loss was not significantly different between the groups (p = 0.765). Stapler hepatectomy was associated with significantly shorter operation time (p = 0.028). Neither postoperative death nor bile leakage occurred, and no reoperation due to hemorrhage was needed in any patient. - Conclusion - This is the first comparison of transection techniques in pediatric liver resection and the first report on stapler hepatectomy in children. All three techniques can be safely applied and may harbor individual advantages in pediatric hepatectomy each.